The Concept of Artificial Intelligence in Justice - Karmaza, Oleksandra; Koroied, Sergii; Makhinchuk, Vitalii; Strilko, Valentyna; Iosypenko, Solomiia (Law, State and Telecommunications Review, 2023)
[Purpose] The aim of the article is to cover the main definitions of the concept of artificial intelligence, its origins, characteristics, grounds for application, as well as direct interaction and influence on the implementation of the main tasks of justice through the use and development of artificial intelligence in the judicial procedure. [Methodology/Approach/Design] To solve the tasks set, the study employed the appropriate methods and materials of scientific research, namely dialectical, historical, statistical, sociological, and other methods of cognition of processes and phenomena, including specialised methods of grammatical consideration and interpretation of legal norms. Furthermore, an entire block of logical methods was used, including classification (upon creating a complete classification and structuring of scientific hypotheses and assumptions), extrapolation, induction and deduction, analogy, abstraction, comparison. [Findings] This paper investigates the emergence and transformation of artificial intelligence in modern technological and information relations, its gradual introduction in various spheres of life, namely the ways of implementation and the possibility of application in justice. Furthermore, the study analyses possible ways and legal consequences of introducing artificial intelligence into the e-justice system in Ukraine and proposes the stages of reformation. [Practical Implications] The materials of this study are of practical value in the implementation of the goals set for the active use of artificial intelligence tools and their gradual improvement, including the development of methodological guidelines, legislative acts covering the judicial procedure and reference books and recommendations for the interpretation of regulations that have already been adopted in the process of introducing electronic justice in the country.